Simulation of Residual Stresses in Surface and Subsurface Layer after Machining - Czan, Andrej; Sajgalik, Michal; Holubjak, Jozef; Piesova, Marianna; Czanova, Tatiana (Communications - Scientific Letters of the University of Zilina, 2016)
This article deals with non-destructive detection method of residual stress as analytical tool of expected distribution of residual stress in surface and sub-surface layers. Based on measurements, which can consists of cloud of points, lines or surface map of residual stress, we can simulate potential distribution of residual stress in surface and subsurface layers via mathematical-statistical procedures. Right identification of residual stress and its distribution can improve the prediction of failures and similar damage incidences due to workload over lifetime of components and also, it can be used as evaluation parameter of suitability of applied manufacturing technological operations.
Keywords: X-ray diffractometry; residual stress; non-destructive detection method; simulation of distribution